2018
DOI: 10.4103/ajns.ajns_125_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phenytoin versus levetiracetam in early seizure prophylaxis after traumatic brain injury, at a tertiary care hospital in Karachi, Pakistan

Abstract: Aims:The aim of the study was to compare the efficacy of phenytoin and levetiracetam for seizure prophylaxis in patients with severe traumatic brain injury (TBI).Subjects and Methods:A randomized controlled trial was conducted over a period of 6 months, at a tertiary health care center in Karachi, Pakistan. Patients with TBI were divided into two groups. Patients in Group A were given phenytoin, whereas Group B patients received levetiracetam. The first dose of the drugs was given within 24 h of injury and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…An additional 53 articles were excluded as these did not meet the eligibility criteria of this meta-analysis. Finally, 25 articles with a total sample size of 6,466 cases were included in the network meta-analysis, including seven randomized controlled trials ( Young et al, 1983a ; Young et al, 1983b ; Temkin et al, 1990 ; Temkin et al, 1999 ; Szaflarski et al, 2010 ; Khan et al, 2016 ; Younus et al, 2018 ), four prospective studies ( Jones et al, 2008 ; Inaba et al, 2013 ; Gabriel and Rowe, 2014 ; Khor et al, 2018 ), 13 retrospective studies ( Wohns and Wyler, 1979 ; Servit and Musil, 1981 ; Ma et al, 2010 ; Debenham et al, 2011 ; Caballero et al, 2013 ; Kruer et al, 2013 ; Bhullar et al, 2014 ; Javed et al, 2016 ; Zangbar et al, 2016 ; Hazama et al, 2018 ; Kwon et al, 2019 ; Harris et al, 2020 ; Nguyen et al, 2021 ), and one non-randomized trial ( Klein et al, 2012 ) as shown in Figure 1 . The characteristics of the study design, interventions, and sample size for each treatment group are summarized in ( Tables 1 , 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional 53 articles were excluded as these did not meet the eligibility criteria of this meta-analysis. Finally, 25 articles with a total sample size of 6,466 cases were included in the network meta-analysis, including seven randomized controlled trials ( Young et al, 1983a ; Young et al, 1983b ; Temkin et al, 1990 ; Temkin et al, 1999 ; Szaflarski et al, 2010 ; Khan et al, 2016 ; Younus et al, 2018 ), four prospective studies ( Jones et al, 2008 ; Inaba et al, 2013 ; Gabriel and Rowe, 2014 ; Khor et al, 2018 ), 13 retrospective studies ( Wohns and Wyler, 1979 ; Servit and Musil, 1981 ; Ma et al, 2010 ; Debenham et al, 2011 ; Caballero et al, 2013 ; Kruer et al, 2013 ; Bhullar et al, 2014 ; Javed et al, 2016 ; Zangbar et al, 2016 ; Hazama et al, 2018 ; Kwon et al, 2019 ; Harris et al, 2020 ; Nguyen et al, 2021 ), and one non-randomized trial ( Klein et al, 2012 ) as shown in Figure 1 . The characteristics of the study design, interventions, and sample size for each treatment group are summarized in ( Tables 1 , 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The study by Temkin et al (1990 ) was not blinded at trial implementation and outcome assessment, while the study by Szaflarski et al (2010 ) was not blinded at outcome assessment. We could not determine whether the blinding method in the studies by Khan et al (2016 ) and Younus et al (2018 ) was correctly implemented during the intervention and evaluation of the outcome measures. Since it was not possible to determine the level of bias in the included randomized controlled studies, the quality of the studies was classified as moderate ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1844 abstracts were excluded due to the following reasons: no study on TBI ( n = 785), no RCT ( n = 431), laboratory study ( n = 88), delayed intervention (e.g., study on rehabilitation techniques; n = 300), no original article ( n = 222), other reasons ( n = 18).During the further analysis of the 82 studies left, five studies had to be excluded, as the full-text revealed that the studies did not meet the criteria of RCTs; two more articles had to be excluded as the full-texts were only available in Russian/Chinese; three articles were identified as review articles. Therefore, a total of 72 articles [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58...…”
Section: Resultsmentioning
confidence: 99%
“…For four studies, no impact factor of the publishing journal was listed [ 16 , 38 , 39 , 40 , 76 , 77 ]. Further, 11 articles were not available through the Web of Science database search at all [ 12 , 15 , 33 , 41 , 51 , 55 , 56 , 66 , 74 , 79 , 81 ]. Details on the studies, including specific interventions, number of patients and outcome measures, are attached as a Supplemental Data File .…”
Section: Resultsmentioning
confidence: 99%
“…Although there has been little agreement on whether traditional frequency bands are certainly fixed entities, each frequency band has been associated with different cognitive functions (Younus et al, 2018 ). Interpreting frequency-dependent network changes in epilepsy provides valuable information.…”
Section: Discussionmentioning
confidence: 99%